Aplikasi Wavelet Untuk Penghilangan Derau Isyarat Elektrokardiograf - Widodo, Bernardinus Sri (Universitas Atma Jaya Yogyakarta, 2011)
Abstract. Wavelet Application For Denoising Electrocardiograph Signal. Wavelet has the advantage of the ability to do multi resolution analysis in which one of its applications is to diminish noises. The major wavelet was selected and some experiments were conducted to find out the scale from 1 to 6. Furthermore, some other continuous experiments were carried out to determine the level of optimal decomposition and wavelet reconstruction. From the research, the findings showed that the selection of the scale from 1-6 did not influence the result significantly. On the other side, from the experiment of the selection of decomposition and reconstruction level, the eighth level was the most optimum level. The result of diminishing noises on the EKG signals using wavelet was slightly seen. From 48 data samples, the average of diminishing noises was 36.20 dB. Keywords: Signal Processing, Wavelet Application, ECG denoising Abstrak. Wavelet memiliki keuntungan dari kemampuan untuk melakukan analisis multi-resolusi di mana salah satu aplikasi adalah untuk mengurangi suara. Wavelet utama adalah dipilih dan beberapa eksperimen dilakukan untuk mengetahui skala dari 1 sampai 6. Selain itu, beberapa percobaan kontinyu lainnya dilakukan untuk menentukan tingkat dekomposisi dan rekonstruksi wavelet yang optimal. Dari penelitian, temuan menunjukkan bahwa pemilihan skala 1-6 tidak mempengaruhi hasil secara signifikan. Di sisi lain, dari eksperimen pemilihan tingkat dekomposisi dan rekonstruksi, tingkat kedelapan tingkat yang paling optimal. Hasil suara mengurangi pada sinyal EKG menggunakan wavelet sedikit terlihat. Dari 48 sampel data, rata-rata suara berkurang adalah 36,20 dB. Kata Kunci: Pengolahan Sinyal, Aplikasi Wavelet, EKG denoising